Formulation and evaluation of gastro-retentive drug delivery system of proponolol HCL - K. Swetha; N. Jhancy laxmi bai; N. Sriram (International Journal of Pharmacy and Analytical Research, 2019)
This study was conducted to develop gastro retentive floating tablets for Propronolol Hcl is a sulfonylurea used in the treatment of hyperglycemia. Which has rapid and complete absorption after oral administration. Diseased state (Hypertension) influences the gastric emptying rate. The recommended adult oral dosage Propronolol HCl is 100 mg once daily. In present study floating tablets were prepared by using natural polymers as floating agents so as to maintain in buoyancy condition for about 12 hours to achieve maximum bioavailability and to produce local bioavailability. Floating tablets were developed by using natural polymer i.e., Xanthum gum, HPC, and HPMCK4 M. Various precompression parameters were evaluated for formulation blend including Drug excipient compatibility studies by using FTIR studies. Calibration curve was plotted by using 0.1 N HCl as medium. The prepared formulations were evaluated for various post compression parameters like hardness, friability, thickness, weight variation, floating lag time floating buoyancy studies and invitro dissolution studies. Among all the formulations F2 formulation which contains Xanthane gum has shown desired percentage drug release in 12 hours. The In vitro dissolution data were fitted in different kinetic models viz. zero order, first order, Higuchi and Korsemeyer - Peppas equation. Correlation coefficients of formulation F2 showed higher correlation with Peppas R2 = 0.993.